PEMASARAN WORTEL DI DESA BATURITI, KECAMATAN BATURITI KABUPATEN TABANAN - Martina Anye; Cening Kardi; I Made Tamba; Ni Putu Anglila Amaral (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The purpose of this research is to:(1) Analyze the product marketing channel system carrots in Baturiti Village, Baturiti District, Tabanan Regency, (2) Analyzesis cost profit and marketing margin of carrot products in Baturiti Village Baturiti Subdistrict Tabanan Regency(3) Analyzing farmer share and efficiency carrot product marketing Baturiti Village Baturiti District Tabanan. Determination of carrot trader respondents using snowball sampling, and determining the respondents of carrot farmers using the sensus method with the total number of respondents in this study amounting to 69 people. Data were analyzed using marketing margin analysis, revenue merchant, merchant profit. Jarnmer Share, and marketing efficiency Based on the research results, the marketing channel in the research area consists of three marketing channels, namely Channel 1: Petan1-Gatherers-Retailers-Consumers Farmer-Retailer-Consumer Channel and Farmer-Consumer Channel. Carrot marketing benefits channel I with a profit of IDR 459000. Meanwhile, the profit of channel 1 marketing is profit of IDR 84000. farmer share channel I is 64.20, Farmer share on channel il is 1.4, farmer share on channel III is 10000 Channel I marketing efficiency is U293 and efficiency1 for marketing channel I is 0432